Analysis of the garbage truck market of Ukraine - Bredun, Viktor (Academic journal Industrial Machine Building Civil Engineering, 2022)
In this work, with the help of object-oriented statistical analysis of the offers of specialized equipment of domestic manufacturers, the compliance of the specialized transport and technological support offered by the market with the needs of the long-term planning of waste management systems at the local and regional levels are established. The range of their products cannot always ensure maximum logistical efficiency when implementing separate collection technologies due to the low presence of offers of garbage trucks with multi-section bodies. When implementing a cluster strategy, which involves the organization of multi-stage transportation of solid waste, there is a danger of a shortage of specialized transport garbage trucks